Factors Associated with Migration of Bangladeshi Doctors Abroad (Bangladesh Journal of Medical Education, 2025)
Background: Physicians’ migration is a global problem with significant impact on health and economy. Migration to developed countries seems to be an adored destination for the physicians of developing countries like Bangladesh and on the other hand tolling the finance and education system of the developing countries. Methods: This qualitative study was conducted among 10 emigrant physicians of Bangladesh selected by snow ball sampling. Data were collected by in-depth interview using interview schedule over a period of 12 months from July, 2023 to June, 2024. The responses were recorded in audio visual recording with the permission of interviewee and it was immediately transcript by the interviewer and the responses were analyzed with Atlas.ti. The themes and subthemes were identified and responses regarding each of them were separately coded and important verbatim were recorded. Data were presented in narrative form. Results: Data were collected focusing on five major issues: factors for migration, challenges after migration, satisfaction with the decision of migration, advice to a doctor who intends to migrate and suggested changes for curriculum. The discussion regarding the factors for migration revealed five major themes: sociopolitical factors, academic factors, economic factors, family related factors and personal factors. Socio-political theme was further divided into subthemes during discussion as political and bureaucratic dependency, interference in career progression poor working condition and insecurity in professional environment. Academic theme was discussed under the sub themes as: career pathway, academic guidance, standard and practical oriented training & examination system and protocol based treatment. Regarding economic them, two major sub themes were revealed, payment during training period and fixed salary not related to workload. Family related theme was extracted into schooling of children, health care for family, provision for quality family time, social support for working mother. Personal factors that were discussed during the sessions were social attitude to junior doctors, differential attitude to the doctors and lack of general modesty and empathy. Conclusions: The insight obtained from the study is a basic framework upon which an extensive quantitative study can be launched and strategies to fight this phenomenon of migration.BJME, Volume-16, Issue-02, July 2025: 29-38